Cartilage stem cells: tools for joint repair? - Archer, Charles (Henry Stewart Talks, 2007)
Cartilage repair, Cartilage progenitor isolation and characterization, Human articular cartilage progenitors, The role of Delta/Notch signalling in progenitor proliferation